2020
DOI: 10.1038/s41467-020-18985-6
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide translational profiling of amygdala Crh-expressing neurons reveals role for CREB in fear extinction learning

Abstract: Fear and extinction learning are adaptive processes caused by molecular changes in specific neural circuits. Neurons expressing the corticotropin-releasing hormone gene (Crh) in central amygdala (CeA) are implicated in threat regulation, yet little is known of cell type-specific gene pathways mediating adaptive learning. We translationally profiled the transcriptome of CeA Crh-expressing cells (Crh neurons) after fear conditioning or extinction in mice using translating ribosome affinity purification (TRAP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 85 publications
5
20
0
1
Order By: Relevance
“…Finally, we observed that fear conditioning per se (in the presence of an adaptive extinction), without optogenetic stimulation, was not greatly associated with gene expression in amygdala pyramidal neurons ( Figure 6 D,E, Table 4 ), in line with PCA highlighting poor segregation between SHAM FEAR vs. SHAM NOT FEAR groups. This result is in line with those reported by McCullough and colleagues [ 41 ] who described a weak separation between the transcriptomes of fear- and not fear-conditioned animals. The authors discussed their findings as result of stress-induced translational changes due to the handling of animals and CS exposure.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Finally, we observed that fear conditioning per se (in the presence of an adaptive extinction), without optogenetic stimulation, was not greatly associated with gene expression in amygdala pyramidal neurons ( Figure 6 D,E, Table 4 ), in line with PCA highlighting poor segregation between SHAM FEAR vs. SHAM NOT FEAR groups. This result is in line with those reported by McCullough and colleagues [ 41 ] who described a weak separation between the transcriptomes of fear- and not fear-conditioned animals. The authors discussed their findings as result of stress-induced translational changes due to the handling of animals and CS exposure.…”
Section: Discussionsupporting
confidence: 93%
“…The present findings indicate that impaired extinction is featured by specific changes of transcriptome that validate previous findings [ 41 ], provide targets for future translational research into cell type-specific control of fear extinction, and emphasize the key role of pyramidal neurons belonging to fear matrix. This type of comprehensive cell-type specific analysis may produce an important array of targets potentially useful for diagnosis, treatment, and prevention of fear-related disorders.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations